Associations Between Residential Exposure to Volatile Organic Compounds and Liver Injury Markers - Wahlang, Banrida; Gripshover, Tyler C; Gao, Hong; Krivokhizhina, Tatiana; Keith, Rachel J; Sithu, Israel D; Rai, Shesh N; Bhatnagar, Aruni; McClain, Craig J; Srivastava, Sanjay; Cave, Mathew C (Toxicological sciences, 2021)
Abstract Occupational exposures to volatile organic compounds (VOCs) have been associated with numerous health complications including steatohepatitis and liver cancer. However, the potential impact of environmental/residential VOC exposures on liver health and function is largely unknown. To address this knowledge gap, the objective of this cross-sectional study is to investigate associations between VOCs and liver injury biomarkers in community residents. Subjects were recruited from six Louisville neighborhoods, and informed consent was obtained. Exposure biomarkers included 16 creatinine-adjusted urinary metabolites corresponding to 12 parent VOCs. Serological disease biomarkers measured included cytokertain-18 (K18 M65 and M30), liver enzymes, and direct bilirubin. Associations between exposure and disease biomarkers were assessed using generalized linear models. Smoking status was confirmed through urinary cotinine levels. The population comprised of approximately 60% females and 40% males; White persons accounted 78% of the population; with more nonsmokers (n = 413) than smokers (n = 250). When compared with nonsmokers, males (45%) and Black persons (26%) were more likely to be smokers. In the overall population, metabolites of acrolein, acrylonitrile, acrylamide, 1,3-butadiene, crotonaldehyde, styrene, and xylene were positively associated with alkaline phosphatase. These associations persisted in smokers, with the exception of crotonaldehyde, and addition of N,N-dimethylformamide and propylene oxide metabolites. Although no positive associations were observed for K18 M30, the benzene metabolite was positively associated with bilirubin, irrespective of smoking status. Taken together, the results demonstrated that selected VOCs were positively associated with liver injury biomarkers. These findings will enable better risk assessment and identification of populations vulnerable to liver disease.